FEATURES OF NK-CELL CONTENTS IN PATIENTS WITH CHRONIC HEPATITIS C - M. S. Selkova; O. V. Nikitina; V. A. Mikhailova; E. V. Esaulenko; A.V. Seliutin (Медицинская иммунология, 2014)
Abstract. Clinical course and outcomes in chronic hepatitis C (CHC) depend on the state of cellular immunity in the patients. We have analyzed some indexes bearing on absolute and relative contents of NK-cells (CD3-CD16+CD56+), and their activated forms (CD3-CD16+CD56+CD107+a), as estimated by the LAMP-protein (CD107a) expression in peripheral blood of seventy patients with verified diagnosis of CHC. A significant reduction in cytotoxic potential of NK cells was revealed in patients with chronic hepatitis C, in spite of normal absolute amounts of total NK-cells. It was revealed that the levels of NK-cells and their activated forms did not did not depend on HCV genotype (1 vs 3). Likewise, they did not differ between the patients with higher and lower viral load. When analyzing relationships between the contents of activated NK cells and levels of biochemical markers of cytolytic and cholestatic syndromes, we have found a direct correlation with AST activity, and an inverse correlation with the of GGT and alkaline phosphatase activities. The data suggest a possible role of altered NK cell activation in pathogenesis of chronic hepatitis C.